2004
DOI: 10.1023/b:jobp.0000016438.86794.8e
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Analysis of DNA Bending Profiles reveals Structural Constraints on the Evolution of Genomic Sequences

Abstract: Abstract. Analyses of genomic DNA sequences have shown in previous works that base pairs are correlated at large distances with scale-invariant statistical properties. We show in the present study that these correlations between nucleotides (letters) result in fact from long-range correlations (LRC) between sequence-dependent DNA structural elements (words) involved in the packaging of DNA in chromatin. Using the wavelet transform technique, we perform a comparative analysis of the DNA text and of the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 151 publications
1
17
0
Order By: Relevance
“…As previously reported in subsection 'Modelling of in vivo nucleosome occupancy data in S. cerevisiae' (Figure 33), this statistical nucleosome ordering can also be diagnosed from the periodic modulations observed in the auto-correlation function C( s) = δY (s)δY (s + s) . But in addition and very importantly, when plotted in a logarithmic representation, the power spectrum displays a very convincing power law decay S(k) ∝ k −ν , with exponent ν = 2H − 1 = 0.74 ± 0.02 (H = 0.87) that is likely to be a direct consequence of the large-scale (low frequency k < 1/200) LRC regime observed in the yeast DNA bending profile in Audit et al (2001Audit et al ( , 2002Audit et al ( , 2004.…”
Section: Long-range Correlationsmentioning
confidence: 86%
See 2 more Smart Citations
“…As previously reported in subsection 'Modelling of in vivo nucleosome occupancy data in S. cerevisiae' (Figure 33), this statistical nucleosome ordering can also be diagnosed from the periodic modulations observed in the auto-correlation function C( s) = δY (s)δY (s + s) . But in addition and very importantly, when plotted in a logarithmic representation, the power spectrum displays a very convincing power law decay S(k) ∝ k −ν , with exponent ν = 2H − 1 = 0.74 ± 0.02 (H = 0.87) that is likely to be a direct consequence of the large-scale (low frequency k < 1/200) LRC regime observed in the yeast DNA bending profile in Audit et al (2001Audit et al ( , 2002Audit et al ( , 2004.…”
Section: Long-range Correlationsmentioning
confidence: 86%
“…As illustrated in Figure 41(b), this simply means that nucleosomes adapt themselves better on sequences that display a 10 bp periodicity with AA/TT/AT that oscillate in phase with each other and facing the minor groove, and out of phase with GC facing the major groove. As originally pointed out in Audit et al (2001Audit et al ( , 2002Audit et al ( , 2004, when performing time-frequency analysis of eukaryotic genomic sequences using either dinucleotide codings or more elaborated di-or tri-nucleotide experimental tables coding for the structural and/or bending properties of the DNA double helix, there is no significant peak that emerges in the power spectrum at the frequency 1/10 bp −1 . This confirms that if locally the 10 bp periodicity sketched in Figure 41(b) can help to phase and position some nucleosomes, at the genome scale this periodicity is clearly not exploited to position the majority of well-defined nucleosomes observed in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As such, wavelets are far better suited to detect domain-type behaviors that span discrete genomic intervals. Wavelets have been used for the analysis of genomic data to uncover local periodic patterns in DNA-bending profiles (Audit et al 2004) and gene-expression data (Allen et al 2003;Jeong et al 2004) to predict protein structures (Lio and Vannucci 2000) and to correlate a variety of genomic data on multiple scales in microbial genomes (Allen et al 2006), and a variety of other applications (Lio 2003).…”
Section: Data Types and Scalementioning
confidence: 99%
“…In order to detect such long-range periodic patterns in inherently noisy chromosome positiondependent data, wavelet analysis has been used in several studies [13,15] (Figure 1). This method has previously been used to detect patterns in gene orientation [14], DNAbending profiles [16], and gene expression data [17,18] in prokaryotes, as well as GC/AT skew oscillations in human chromosomes [19]. These studies have revealed that genome sequences are generally nonrandom with respect to chromosome position, and that long-range correlations in certain properties (e.g., gene orientation; [14]) exist across many different length-scales.…”
Section: Introductionmentioning
confidence: 99%